Garlic Mixed Olive Oil Cream Formulation and Its Activity Against A Clinical Isolate of Staphylococcus aureus - Khairan, Khairan; Zahraty, Ifrah; Idroes, Rinaldi (Journal of Carbazon, 2023)
Garlic or Allium sativum is known containing of organosulphur compounds. These compounds are known have potential as antimicrobial, antivirus, and anticancer. The purpose of this study is to determine the activity of garlic mixed olive oil (GMO2) cream against the clinical isolate of Staphylococcus aureus and its evaluation by observing the organoleptic, homogeneity, pH, spread ability, stickiness, and viscosity. The result showed that GMO2 was able to inhibit the growth of Staphylococcus aureus bacteria at concentrations of 25 and 50 mg/ml. Meanwhile, the formulation of GMO2 cream at concentration 25 mg/ml was done by poisoned food method showed no activity against clinical isolate of Staphylococcus aureus. In this study, vanishing cream was used as negative control. The evaluation of GMO2 cream at concentration of 25 mg/mL has stability in organoleptic and homogeneity after the cycling test. The pH value of GMO2 cream was approximately equal to vanishing cream. The results of spread ability and stickiness tests indicated that GMO2 cream had the spreading and sticking strength which satisfied with the standard cream in range 5-7 and 4 respectively. The viscosity value of GMO2 cream were decreased after the cycling test. The stability test result showed that of GMO2 cream was stable after the cycling test.